2017
DOI: 10.4103/0366-6999.200545
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Postpartum Hemorrhage Requiring Massive Transfusions at a Tertiary Center

Abstract: Background:The reports on massive transfusions (MTs) in obstetrics have recently been an increasing trend. We aimed to define the clinical features, risk factors, main causes, and outcomes of MTs due to severe postpartum hemorrhage (PPH) and the frequency trends over the past 10 years.Methods:We retrospectively analyzed the data of 3552 PPH patients who were at ≥28 weeks of gestation in the Obstetric Department of Peking University First Hospital from January 2006 to February 2015. The clinical records of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…During the last 3 years, the mentioned hospitals have had about 75,000 births per year, which the highest birth rate was nested into Malalai Zijenton Hospital and the lowest birth rate was nested into the 102 bed Khair Khana hospital, 26,500 deliveries per year and 13,439 deliveries per year, respectively. The number of cesarean sections in these Hospitals accounts for 15 The population of this study consisted of all patients who delivered between August 2018 and October 2018, during the study period, and they were hospitalized in mentioned hospitals at the time of the study. The inclusion criteria included women who delivered in these four governmental hospitals or at home, and had primary PPH after normal vaginal delivery or cesarean section, within 24 h after birth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last 3 years, the mentioned hospitals have had about 75,000 births per year, which the highest birth rate was nested into Malalai Zijenton Hospital and the lowest birth rate was nested into the 102 bed Khair Khana hospital, 26,500 deliveries per year and 13,439 deliveries per year, respectively. The number of cesarean sections in these Hospitals accounts for 15 The population of this study consisted of all patients who delivered between August 2018 and October 2018, during the study period, and they were hospitalized in mentioned hospitals at the time of the study. The inclusion criteria included women who delivered in these four governmental hospitals or at home, and had primary PPH after normal vaginal delivery or cesarean section, within 24 h after birth.…”
Section: Methodsmentioning
confidence: 99%
“…Some diseases have association with PPH including blood transfusion, renal failure, coagulation deficiencies and are also associated with long-term morbidities, including anemia, hysterectomy. Moreover, with other surgical procedures to reduce blood flow to the uterus and their subsequent consequences, infertility has to be considered as a consequence of PPH, although it is difficult to quantify their burden [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…10 However, only two small studies focused on obstetric MBT in China. 14 15 . One study concluded that the incidence of MBT in relation to PPH was stable (25-27 per 10 000 maternities) during 2006-2015.…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics, maternal postpartum hemorrhage is >400 mL in 24.2% of cases [2]. Many reasons are reported to contribute to maternal postpartum hemorrhage, among which one of the main reasons is uterine atony [3]. Therefore, a series of measures are needed in clinic to enhance uterine contractility in pregnant women to reduce their perinatal risk.…”
Section: Introductionmentioning
confidence: 99%